Dampak Putusan Mahkamah Konstitusi No. 90/PUU-XXI/2023 mengenai Batas Usia Cawapres dan Dinamika Demokrasi Konstitusional - Rafiqatul Haniah (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The Constitutional Court Decision Number 90/PUU-XXI/2023 on the age requirement for presidential and vice-presidential candidates has generated significant public debate in Indonesia. The decision reinterprets the candidacy requirement by allowing individuals under the age of 40 to run for President or Vice President, provided that they have previously or currently held an elected regional executive position. This article employs a normative legal research method, using statutory and conceptual approaches to examine the implications of the decision. The study finds that the decision has produced both opportunities and challenges. On the one hand, it expands political participation for younger leaders with electoral experience. On the other hand, it raises concerns regarding constitutional interpretation, institutional authority, electoral fairness, and public trust in the Constitutional Court. Therefore, Constitutional Court Decision Number 90/PUU-XXI/2023 should not be viewed merely as a change in candidacy requirements, but also as a legal event with broader implications for constitutional democracy and Indonesia’s state administration system.